Barreiras e facilitadores na transição de via de antimicrobianos sob a ótica de enfermeiros, farmacêuticos e médicos - Flausino, Tatiane Garcia do Carmo (Universidade Federal de São Carlos, 2023)
Antimicrobial resistance is one of the most important public health problems worldwide, with a great impact on morbidity, mortality, and health costs. In this context, Antimicrobial Stewardship Programs (ASP) act as an important tool in order to improve clinical outcomes, reduce costs and adverse events, and contribute to the reduction of antimicrobial resistance. Among the strategies provided for in these programs, the switch intravenous to oral route of the antimicrobial therapy in use consists of a low-cost intervention with great potential to generate savings and minimize risks to the patient. However, as the literature points out, the switch therapy does not always occur at an opportune moment. Thus, the present study aimed to develop a questionnaire to identify barriers and facilitators in the switch intravenous to oral antimicrobial, from the perspective of nurses, pharmacists and physicians, actors directly related to antimicrobial therapy. This is a descriptive study carried out in stages, the first of which is responsible for identifying the relevant content for the switch therapy, through a remote, semi-structured interview with two nurses, two pharmacists, and two infectologists. Next, a questionnaire was developed, based on the theoretical construct generated in the previous step, with 15 closed questions, divided into five domains. Finally, this instrument was made available on an online platform and 167 responses were received from the target audience, 79 (47.3%) pharmacists, 71 (42.5%) nurses, and 17 (10.2%) physicians. The main barriers pointed out by the participants were the absence of medication with adequate oral bioavailability (76%), lack of engagement by prescribers (74%), oral medication not available at the institution (74%) and lack of knowledge on the subject (71%). With regard to the main facilitators, the possibility of hospital discharge (85%), the hospital infection control service working at the institution (82%), cost (81%) and ease of administering the medication orally (77%) were pointed out. The present study made it possible to identify the barriers and facilitators for switching antimicrobial therapy from the perspective of the professionals directly involved. The identification of these barriers can contribute to the development of strategies, at the institutional level, within ASP, so that switch therapy happens in a timely and safe way.
Barriers and facilitators in the switch intravenous to oral antimicrobial, from the perspective of nurses, pharmacists and physicians
Keywords: Programa de gerenciamento de antimicrobianos; Vias de administração de medicamentos; Resistência microbiana a medicamentos; Inquéritos e questionários; Antimicrobial stewardship program; Drug administration routes; Drug resistante, microbial; Surveys and questionnaires; CIENCIAS DA SAUDE